Favela eviction policies: Old practices, new justifications. The case of the favelas located in the Alto da Boa Vista district (Rio de Janeiro, Brazil) and the conservative instrumentalization of environmental issues - Fonseca, Tiago Boruchovitch (2020)
This paper aims to analyze the conflicts that threaten of eviction the favelas located in the Alto da Boa Vista neighborhood in Rio de Janeiro, Brazil, from the history of the policies of favelas removal in this municipality. The Alto da Boa Vista neighborhood is placed in the Tijuca Massif, consisting of the immediate surroundings of the Tijuca National Park. It is characterized by great social contrasts, having in its formal part several houses of high standard, as well as thirteen favelas. These favelas located in this neighborhood are threatened of eviction by two main fronts: a law project to implement an Environmental Protection and Urban Recovery Area and a Public Civil Action carried out by the State Public Prosecutor's Office of Rio de Janeiro. These two conflicts are based on justifications related to environmental issues, whether due to environmental risk or degradation, built from fragile arguments in both cases. Thus, it is intended to carry out a brief history of the favela removal policies in the city of Rio de Janeiro, bringing also the achievements related to the right to housing and permanence, as a way of contextualizing and reflecting on the appearance of environmental justifications for the eviction threats suffered by the favelas of Alto da Boa Vista.